SYNTHESIS OF THE ORGANIZATIONAL STRUCTURE OF THE MANAGEMENT BODY OF THE INFORMATION AND TELECOMMUNICATION NETWORK - БОВДА, Едуард; ЛЮБАРСЬКИЙ, Сергій; КЛИМЕНКО, Віктор; САМОХВАЛОВ, Юрій (Київський національний університет імені Тараса Шевченка, 2024)
An approach to solving the problem of synthesizing the organizational structure of the management body of the information and telecommunications network based on the suboptimization method is proposed. The statement of the synthesis problem is presented, the objective function, limitations, partial quality indicators and factors influencing them are defined. The issue of optimizing the working conditions of officials and the choice of technical means of communication was also considered.

Запропоновано підхід до розв'язання задачі синтезу організаційної структури органу управління інформаційно-телекомунікаційної мережі на основі методу субоптимізації. Наведено постановку задачі синтезу, визначено цільову функцію, обмеження, часткові показники якості та чинники, що впливають на них. Розглянуто питання оптимізації умов діяльності посадових осіб і вибору технічних засобів комунікації.
СИНТЕЗ ОРГАНІЗАЦІЙНОЇ СТРУКТУРИ ОРГАНУ УПРАВЛІННЯ ІНФОРМАЦІЙНО-ТЕЛЕКОМУНІКАЦІЙНОЇ МЕРЕЖІ
Keywords: information and telecommunication network; suboptimization method; synthesis of organizational structure; інформаційно-телекомунікаційна мережа; метод субоптимізації; синтез організаційної структури